A prospective observational study on bolus administration of high-dose nitroglycerin in treating sympathetic collapsing acute pulmonary oedema - Marndi, Chhatray; Behera, Ashok Kumar; Patra, Gopabandhu; Chhotaray, Saubhagya (International Journal of Research in Medical Sciences, 2023)
Background: Sympathetic crashing causes sudden cardiac failure in minutes or hours. Early diagnosis and treatment may avoid acute heart failure fatalities. Sympathetic crashing reduces afterload, shifting fluid into the pulmonary circulation and causing pulmonary edema. The usual strategy of progressively increasing vasodilator dosage has increased preload. Treating SCAPE with large doses of nitroglycerin and non-invasive breathing is helpful. High doses of nitroglycerin boost afterload and eliminate ICU admissions. In this study, a standard protocol for the treatment of patients with sympathetic crashing acute pulmonary edema is assessed for its effectiveness. Methods: An observational study was conducted prospectively at Bhima Bhoi Medical College and Hospital in Balangir, Odisha, India over the course of a year. The patients presenting with SCAPE symptoms were treated according to standard protocol. The outcomes were subjected to statistical analysis to derive a correlation between treatment and response. Results: The mean initial bolus given to all the patients was 836 µg. The total cumulative dose of nitroglycerin used in each patient was 36 mg. The symptoms of most of the patients resolved within the first 6 hours of treatment. Conclusions: The standard protocol developed at the institute, which included a high dose of nitroglycerine along with non-invasive ventilation, was efficient in treating acute heart failure due to sympathetic crashing and acute pulmonary edema. Nitroglycerin, along with non-invasive ventilation, should be used in the management of sympathetic crashing pulmonary edema and acute heart failure.